Teaching interpretation in HUFLIT: On-spot vs on-stage Techniques - Nguyen Duc, Chau (Tạp chí Khoa học HUFLIT, 2024)
During a period of over 20 years, teaching interpretation techniques – relating to a crucial major in the Faculty of Foreign Languages curriculum – have been diligently researched in HUFLIT (Ho Chi Minh City University of Foreign Languages & Information Technology) to find out the better pattern, one of which is how to cope with students’ passive participation, which usually leads to poor performance in the subjects requiring high independence and confidence such as Interpretation. Some literature reviews almost got a concensus about Asian students’ passive attitude in the classroom (Wan, Y., 2021; Takahashi, 2019) [1] including unwillingness to respond, rarely asking questions, and passive participation in classroom activities. Wan, Y. (2021: p1) [1] quoted Tani (2008) [2] “Few studies indicate that low participation will impede students’ academic achievement, but the reticent behavior has been seen as “a barrier to the fostering of good learning practice” and “an obstacle to engaging with campus life and fully benefiting from studying in another country”. However, the above-mentioned behavior has somewhat affected the classroom learning environment and impeded the common advance of the whole. The requirements of the course and the final tests focus on the learners’ confidence, independence, pressure standing, real competence,… needing a change in teaching process. In the narrow scope of the study, the author presents the background of the research, the pros and cons of the on-site and on-stage techniques based on the lecturers’ varied views, some relevant analyses, and some recommendations. Keywords: Teaching interpretation, HUFLIT, Translation-Interpretation, on-site, on-stage.